Nurses’ experiences with virtual care during the COVID-19 pandemic: a qualitative study in primary care - Crystal Vaughan; Lindsay Hedden; Julia Lukewich; Maria Mathews; Emily Gard Marshall; Leslie Meredith; Dana Ryan; Sarah Spencer; Suzanne Braithwaite; Jamie Wickett; Stan Marchuk; Emilie Dufour (BMC Nursing)
Abstract Background During the COVID-19 pandemic, virtual care was used to deliver primary care services. Nurses contributed to primary care teams’ capacity to deliver care virtually. This study explored nurses’ roles in virtual care delivery in primary care and the barriers and facilitators that influenced their contributions. Methods We employed a qualitative descriptive approach and conducted semi-structured interviews with nurses representing each regulatory designation (i.e., Nurse Practitioners, Registered Nurses, Licensed/Registered Practical Nurses) working in primary care in four Canadian provinces (i.e., British Columbia, Ontario, Nova Scotia, and Newfoundland and Labrador). We performed thematic analysis on data related to the delivery of virtual care. Results We interviewed seventy-six nurses and identified three key themes and various sub-themes related to virtual nursing practice during the COVID-19 pandemic: (1) variable adoption of virtual care among nurses, (2) facilitators and barriers to virtual nursing practice, and (3) impacts of virtual delivery on care provision by nurses. Nurses’ involvement in virtual care varied across designations and nurses recalled various facilitators and impediments that influenced their virtual care experience, such as guidance documents, funding models, and the availability of equipment. Virtual care influenced nurses’ workflow, their ability to deliver patient-centred care, and their ability to bridge the care gap. Conclusions Primary care teams are increasingly relying upon nurses to support virtual care delivery, emphasizing the need to understand nursing roles in virtual care. Primary care funding models should be leveraged to support nurses in virtual care delivery; and standardized learning opportunities and guidance documents focused on virtual care should be available to support primary care nurses and strengthen their contributions in future primary care teams that involve virtual nursing care.